Clinical and financial burden of hospitalised community-acquired pneumonia in patients with selected underlying comorbidities in England. Issue 1 (13th October 2020) - Campling, James; Jones, Dylan; Chalmers, James; Jiang, Qin; Vyse, Andrew; Madhava, Harish; Ellsbury, Gillian; Rabe, Adrian; Slack, Mary
Abstract : Background: Hospitalised pneumonia may have long-term clinical and financial impact in adult patients with underlying comorbidities. Methods: We conducted a retrospective cohort study using the Hospital Episode Statistics (HES) database to determine the clinical and financial burden over 3 years of hospitalised community-acquired pneumonia (CAP) to England's National Health Service (NHS). Subjects were adults with six underlying comorbidities (chronic heart disease (CHD); chronic kidney disease (CKD); chronic liver disease (CLD); chronic respiratory disease (CRD); diabetes mellitus (DM) and post bone marrow transplant (post-BMT)) with an inpatient admission in 2012/2013. Patients with CAP in 2013/2014 were followed for 3 years and compared with similarly aged, propensity score-matched adults with the same comorbidity without CAP. Findings: The RR of hospital admissions increased after CAP, ranging from 1.08 (95% CI 1.04 to 1.12) for CKD to 1.38 (95% CI 1.35 to 1.40) for CRD. This increase was maintained for at least 2 years. Mean difference in hospital healthcare costs (£) was higher for CAP patients in 2013/2014; ranging from £1115 for DM to £8444 for BMT, and remained higher for 4/6 groups for 2 more years, ranging from £1907 (95% CI £1573 to £2240) for DM to £11 167 (95% CI £10 847 to £11 486) for CRD.) The OR for mortality was significantly higher for at least 3 years after CAP, ranging from 4.76 (95% CI 4.12 to 5.51, p<0.0001) for CLD to 7.50 (95%CI 4.71 to 11.92, p<0.0001) for BMT. Interpretation: For patients with selected underlying comorbidities, healthcare utilisation, costs and mortality increase for at least 3 years after being hospitalised CAP.